1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<101::aid-sia627>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

XPS of sulphide mineral surfaces: metal-deficient, polysulphides, defects and elemental sulphur

Abstract: This paper reviews evidence for the assignments of components of the S 2p XPS spectra from sulphide mineral surfaces under different conditions of preparation, oxidation and reaction. Evidence from other techniques confirming assignment of high‐binding‐energy S 2p components to metal‐deficient sulphide surfaces, polysulphides, elemental sulphur and electronic defect structures is considered for specific cases. Reliable assignment of S 2p3/2 components at 163.6–164.0 eV to elemental sulphur Sn0 can be confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(207 citation statements)
references
References 23 publications
14
193
0
Order By: Relevance
“…The remaining phase at the surface of the nanocrystal, Pb 1− S, is lead-deficient, aswas confirmed by the high S:Pb atomic ratio obtained through XPS and EDS. Such vacancies induce the sulphur to rebuild as polysulphide (S n 2-) groups, 21,22 which explains why the S-S bond contribution is about 0.7 eV lower than what could be expected for elemental sulphur (S 0 ). The relatively small change in the polysulphide contribution of the methanol-treated sample before exposure to ambient conditions indicates that the lead atoms have not been displaced, and thus, the treatment is successful in the removal of the oleate tails which are passivating/protecting these sites from hydroxylation.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining phase at the surface of the nanocrystal, Pb 1− S, is lead-deficient, aswas confirmed by the high S:Pb atomic ratio obtained through XPS and EDS. Such vacancies induce the sulphur to rebuild as polysulphide (S n 2-) groups, 21,22 which explains why the S-S bond contribution is about 0.7 eV lower than what could be expected for elemental sulphur (S 0 ). The relatively small change in the polysulphide contribution of the methanol-treated sample before exposure to ambient conditions indicates that the lead atoms have not been displaced, and thus, the treatment is successful in the removal of the oleate tails which are passivating/protecting these sites from hydroxylation.…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent studies, Métrich et al (2002Métrich et al ( , 2003 proposed that S 4+ is the important intermediate species for the degassing of excess S in oxidized and H 2 O-rich basaltic arc volcanoes. However, Fleet et al (2005b) also observed a weak peak consistent with a minor to trace amount of sulfi te in a S K-edge XANES spectrum of scapolite, but cautioned that, where sulfi de and sulfate species are present in the bulk sample, sulfi te is a possible product of auto-redox reactions at the sample surface (or near surface) during either sample preparation or XANES measurement (see also Smart et al 1999).…”
Section: Oxyanions Of Sulfurmentioning
confidence: 99%
“…The other doublet at 162.5 eV should be due to a combination of S2 2-from pyrite, S2 2-from chalcopyrite, and Sn 2-from chalcopyrite. Since the positions of these peaks are very close, especially S2 2-from pyrite with S2 2-from chalcopyrite, it is difficult to further decouple them precisely (Smart et al 1999). Furthermore, a broad peak was observed at 168.2 eV in the regrinding product, which is attributed to sulphate SO4 2- (Buckley and Woods 1984).…”
Section: The Separation Of Chalcopyrite From Pyritementioning
confidence: 95%
“…eV is from disulphide S2 2- Schaufuß et al, 1998;Smart et al 1999). An energy loss (EL) feature has been fitted at approximately 164.5 eV, which is associated with S 3p to Fe eg excitation (Schaufuß et al, 1998;Peng et al 2012).…”
Section: Pyrite Flotation After Regrinding With Different Grinding Mediamentioning
confidence: 99%
See 1 more Smart Citation